Gender inequalities in housing policy: Evidence from the popular housing plan of Maringá-PR, Brazil (Desenvolvimento em Questão, 2026)
This article discusses how gender inequalities influenced women’s participation in the elaboration process of the Popular Housing Plan of Maringá. Based on a qualitative approach, the research was developed through document analysis, observation of public meetings, and semi-structured interviews conducted with ten women involved in the participatory process in different positions. The findings reveal a mismatch between the composition of the municipality’s housing demand, predominantly female, and the effective presence of these women in public policy debate spaces. Although formally open, participatory spaces were shaped by barriers related to territory, mobility, care responsibilities, income, race, and the institutional organization of participation itself. The centralization of meetings, transportation costs, everyday overload, and technical language particularly limited the continued participation of women directly affected by housing precarity. The study concludes that the formal existence of participatory mechanisms does not guarantee effective participation when the disparities shaping access to the city and housing continue to operate within public policy itself.
Keywords: Gender inequalities; Housing policy; Women’s participation; Urban inequalities; Maringá